2016
DOI: 10.14260/jemds/2016/1327
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Findings of Preoperative Computerised Tomography of Mastoids With Intraoperative Findings in Cases With Csom

Abstract: BACKGROUNDPatients with chronic suppurative otitis media are very common in Barpeta district of Assam. It is also common and frequent OPD visitors in medical colleges and other hospitals across India. HRCT mastoids play an important role in diagnoses of CSOM, selection of surgical procedures and to know the anatomic details of temporal bone in revision cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
0
2
1
Order By: Relevance
“…10 Nath RK et al found that sensitivity and specificity in respect to ossicular erosion, sinus plate erosion, SCC erosion, facial canal and tegmen plate dehiscence ranges from 70 to100%. 12 Low sensitivity in detection of facial canal dehiscence, labyrinthine fistula and sinus plate erosions was noted in our study, compared to other parameters studied. This can be justified that the soft tissue covering the small defect, which was not so obvious on HRCT scan or it might have developed during progression of the disease over the period of time if the patient was not operated immediately.…”
Section: Discussioncontrasting
confidence: 66%
See 2 more Smart Citations
“…10 Nath RK et al found that sensitivity and specificity in respect to ossicular erosion, sinus plate erosion, SCC erosion, facial canal and tegmen plate dehiscence ranges from 70 to100%. 12 Low sensitivity in detection of facial canal dehiscence, labyrinthine fistula and sinus plate erosions was noted in our study, compared to other parameters studied. This can be justified that the soft tissue covering the small defect, which was not so obvious on HRCT scan or it might have developed during progression of the disease over the period of time if the patient was not operated immediately.…”
Section: Discussioncontrasting
confidence: 66%
“…Nath RK et al found that sensitivity and specificity of 100% with regards to soft tissue masses in mastoids and middle ears. 12 Gomaa et al in a comparative study including 56 patients reported accuracy and sensitivity of HRCT in detecting cholesteatoma (92.8%), its location and extension (96.4%). 13 HRCT was able to detect all patients (38) with malleus intactness.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation